PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING ( CTL ) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IA SDN 144 PEKANBARU - Nurhayati '; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The Research carried out base on the lowly of social SDN 144 Pekanbaru which is about 59,5 within minimal completennees criterion stated is 70 .this Research is classrom Action reseac rh. the purpose of this Research is to improve the outcomes IPS Ia grade students of SD 144 Pekan baru through the implementation of the strategi map concept into the learning process . research carried out in march of academic year 2014/ 2015 In 144 primary school inthe class 1a Pekanbaru .The instrumen used in this study is the teacher and student acttivity sheets as well as learning about the test result. This study present an increase in the activity of teachers in the first cycle of teacher activity75% with the good category , the second cycle increased to 93,75% in Very good Based on the resul of research of student learning outcomes increased visits from the basic score,59.50 to 80,25 in the fist cycle with a percentage increase of 25,85% from the base score cycle II, the average value of 85,00 with the percentage increase of 50,00 %,increase learning outcomes IPS seen from master learning outcomes of students who reach the KKM is 72 on Beach Daily test.Results of this Research indicate that the implementation of the map concept in the learning process IPS can improve the quality of the learning process and learning outcomes.Keywords : Contextual teaching and learning out comes IPS